2009
DOI: 10.1111/j.0105-2896.2009.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive functions of activated B cells in autoimmune diseases reveal the dual roles of Toll‐like receptors in immunity

Abstract: B lymphocytes contribute to immunity through production of antibodies, antigen presentation to T cells, and secretion of cytokines. B cells are generally considered in autoimmune diseases as drivers of pathogenesis. This view is certainly justified, given the successful utilization of the B cell-depleting reagent rituximab in patients with rheumatoid arthritis or other autoimmune pathologies. In a number of cases, however, the depletion of B cells led to an exacerbation of symptoms in patients with autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 122 publications
(229 reference statements)
3
92
0
Order By: Relevance
“…As the human gut contains such large volumes of beneficial bacteria, they constantly trigger the TLRs. This leads to an eventual attenuation in the TLR response [82][83][84], (see Figure 2). …”
Section: Probiotics Applications In Autoimmune Diseases 335mentioning
confidence: 99%
“…As the human gut contains such large volumes of beneficial bacteria, they constantly trigger the TLRs. This leads to an eventual attenuation in the TLR response [82][83][84], (see Figure 2). …”
Section: Probiotics Applications In Autoimmune Diseases 335mentioning
confidence: 99%
“…Some regulatory B cell populations have also been shown to be induced in diverse disease settings and in response to many different exogenous and endogenous stimuli. Toll-like receptor (TLR) signalling via TLR-2, 4 and 9 as well as B cell receptor (BCR) signalling and co-stimulation mediated by CD40, CD80/CD86 or B-cell activating factor (BAFF) has been demonstrated to induce B cells with suppressive activity (Fillatreau, Sweenie et al 2002;Mauri, Gray et al 2003;Blair, Chavez-Rueda et al 2009;Kala, Rhodes et al 2010;Lampropoulou, Calderon-Gomez et al 2010;Yang, Sun et al 2010 (Yanaba, Bouaziz et al 2008). The human equivalent to mouse B10 cells has been identified recently as a small population within peripheral blood CD24 hi CD27 + B cells (Iwata, Matsushita et al 2011).…”
Section: Breg Cell Populations In Mice and Humansmentioning
confidence: 99%
“…Recently, B lymphocytes have attracted growing attention as cells that may influence the development and regulation of not only autoantibody-associated, but also T cell-mediated, autoimmune disorders (1,2). Clinical studies have shown that treatment with Rituximab, a mouse-human chimeric anti-CD20 Ab, which effectively depletes naive and memory B cells from peripheral blood (3,4), is beneficial in many patients with rheumatoid arthritis (5,6), multiple sclerosis (7,8), and type 1 diabetes (9).…”
mentioning
confidence: 99%
“…However, in some patients with these diseases (10,11), and in most patients with ulcerative colitis (12), treatment with Rituximab has led to an exacerbation of symptoms. Likewise, in mice, the depletion of B cells may lead to either amelioration or aggravation of autoimmune manifestations, and in several autoimmune disease models, a congenital lack of B cells is associated with an aggravated course of disease (1,2,6,8,9,(11)(12)(13)(14)(15). Consequently, it appears that similar to T cells, B cells can have dual functions in autoimmune diseases by both contributing to and suppressing disease development or progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation